“russia” with a lowercase letter: A mythological approach - Sabitov, Daniyar (Studia Rossica Posnaniensia, 2025)
This paper examines the contemporary phenomenon of Ukrainians writing the word “Russia” with a lowercase letter in response to Russia’s invasion of Ukraine. This practice has attracted the attention of Ukrainian researchers, who interpret it as a way of expressing emotions such as neglect. However, scholars tend to describe this phenomenon as self-evident without explaining how a change in letter case can convey emotions. A retrospective analysis reveals the evolving function of capital letters in Latin and Cyrillic scripts – from a utilitarian role in text division to the acquisition of their own semantic significance, particularly in the case of proper names. The paper also proposes an interpretation of the lowercase spelling of “russia” using the myth theory developed by Juri Lotman and Boris Uspensky, founders of the Tartu-Moscow Semiotic School. The study argues that altering a proper name is not simply a manipulation of ordinary language but an appeal to a special layer of mythological language. What appears from a descriptive perspective to be a mere renaming is, from the perspective of myth, a redefinition of the object itself. One object (“Russia”) disappears, and its place is taken not by a modified version, but by a fundamentally different object (“russia”).